2010
DOI: 10.1089/scd.2009.0328
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Integrins in Human Induced Pluripotent Stem Cell Growth on Matrigel and Vitronectin

Abstract: Human induced pluripotent stem cells (iPSCs) hold promise as a source of adult-derived, patient-specific pluripotent cells for use in cell-based regenerative therapies. However, current methods of cell culture are tedious and expensive, and the mechanisms underlying cell proliferation are not understood. In this study, we investigated expression and function of iPSC integrin extracellular matrix receptors to better understand the molecular mechanisms of cell adhesion, survival, and proliferation. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
114
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(126 citation statements)
references
References 29 publications
11
114
0
1
Order By: Relevance
“…These combinations, designated in Figure 1 as small orange circles, comprise cell surface receptors for all major ECM components. It was also found, as discussed in the previous section, that attachment through either laminin or RGD binding integrins , (Rodin et al, 2010), (Wong et al, 2010), (Braam et al, 2008), (Rowland et al, 2010), (Yoon et al, 2010), (Yap et al, 2011) is sufficient to support undifferentiated proliferation of hECS in serum-free, chemically defined medium. Fig.…”
Section: Biomimetic Surfaces For Stem Cellsmentioning
confidence: 65%
See 1 more Smart Citation
“…These combinations, designated in Figure 1 as small orange circles, comprise cell surface receptors for all major ECM components. It was also found, as discussed in the previous section, that attachment through either laminin or RGD binding integrins , (Rodin et al, 2010), (Wong et al, 2010), (Braam et al, 2008), (Rowland et al, 2010), (Yoon et al, 2010), (Yap et al, 2011) is sufficient to support undifferentiated proliferation of hECS in serum-free, chemically defined medium. Fig.…”
Section: Biomimetic Surfaces For Stem Cellsmentioning
confidence: 65%
“…The orthologs of human integrins recognizing the RGD amino acid sequence and laminins can be traced back to primitive organisms, while other integrins must have evolved with increasing organism complexity. From such a perspective, it is not surprising that hESCs primarily express integrins recognising the RGD sequence and laminin (Braam et al, 2008), (Meng et al, 2010), (Rowland et al, 2010), (Prowse et al, 2011). Braam et al, evaluated integrin expression in three hESC lines (HES2, HUES1, and HESCNL3) using fluorescence-activated cell sorting analysis.…”
Section: Biomimetic Surfaces For Stem Cellsmentioning
confidence: 99%
“…Farklı integrinlerle etkileşim sonucu ortak bir hücre içi sinyal mekanizmasının ya da alternatif mekanizmaların devreye girerek pluripotent özelliğin uzun süreli kontrolünü sağladığı dü-şünülmektedir. Son dönemde yapılan çalışmalarda besleyici hücrelerle olan kültür sistemlerinde, etkin bir in vitro sistem oluşturulabilmesi için iEKH ile besleyici hücrelerde uygun integrinlerin bulunması gerektiği gösterilmiştir [77][78][79] . Bu yüzden, hücre-lerdeki integrin reseptörlerinin ve buna bağlı sinyal yollarının tanımlanması pluripotent özelliğin uzun süreli korunumu ve uygun in vitro kültür şartlarının oluşturulabilmesi için gereklidir.…”
Section: İnsan Embriyonik Kök Hücre Kültürüunclassified
“…53 a V b 5 is required for initial attachment of hiPSCs to a vitronectin substrate, but once attachment is achieved, the proliferation of these cells is not affected by blocking just a V b 5 with antibodies. 54 The inhibition of these cells' proliferation necessitates the blocking of both a V b 5 and b 1 . 54,55 Similarly, a V b 3 , a 6 b 1 , and a 2 b 1 play a decisive role in the adhesion and proliferation of hESCs on Matrigel substrates.…”
Section: Potential Mechanisms Of Substrate-cell Interactions In Hpsc mentioning
confidence: 99%
“…54 The inhibition of these cells' proliferation necessitates the blocking of both a V b 5 and b 1 . 54,55 Similarly, a V b 3 , a 6 b 1 , and a 2 b 1 play a decisive role in the adhesion and proliferation of hESCs on Matrigel substrates. 56 Quantitative real-time polymerase chain reaction (qRT-PCR) analysis of integrin expression in mESCs indicated that integrins a 5 b 1 , a v b 5 , a 6 b 1 , and a 9 b 1 are involved in the maintenance of pluripotency, indicating that there is significant overlap in patterns of integrin expression between mPSCs and hPSCs.…”
Section: Potential Mechanisms Of Substrate-cell Interactions In Hpsc mentioning
confidence: 99%